Crystal structure of a putrescine aminotransferase from Pseudomonas sp. strain AAC. Issue 1 (1st January 2017) - Wilding, Matthew; Scott, Colin; Newman, Janet; Peat, Thomas S.
Abstract : The crystal structure of a putrescine aminotransferase from Pseudomonas sp. strain AAC has been determined to a resolution of 2.07 Å. Abstract : The putrescine aminotransferase KES24511 from Pseudomonas sp. strain AAC was previously identified as an industrially relevant enzyme based on the discovery that it is able to promiscuously catalyse the transamination of 12‐aminododecanoic acid. Here, the cloning, heterologous expression, purification and successful crystallization of the KES24511 protein are reported, which ultimately generated crystals adopting space group I 2. The crystals diffracted X‐rays to 2.07 Å resolution and data were collected using the microfocus beamline of the Australian Synchrotron. The structure was solved using molecular replacement, with a monomer from PDB entry4a6t as the search model.